Trends in Indian and Russian wrestling: a comparative study - Singh Suhag, N. (International Journal of Wrestling Science, 2020)
This study aimed to have a comparative study of Indian and Russian wrestlers with respect to certain preidentified parameters so as to gain an insight in the analysis of physical, psychological and physiological traits of both set of wrestlers and to identify key features that could be learned by both Russian and Indian wrestlers from each other. All the parameters, which were researched, were divided into three broad categories namely Physical variables, Psychological variables and Physiological variables. The study was undertaken on Men¡¯s Freestyle wrestlers by taking two top level wrestlers with credible past performance and top form from each national team in the six Olympic Wrestling weight divisions of 57kg, 65kg, 74kg, 86kg, 97kg and 125kg. After the collection of values for the purpose of the analyses, the various statistical procedures were employed. The required statistical calculations were computed with the help of SPSS software. The descriptive calculation and ¡°t. test were computed. Among the physical variables that were found significant at 0.05 level of confidence includes . speed, agility, explosive strength, endurance and flexibility. However, in Abdominal Strength no significant difference was seen. Among the psychological parameters, two variables were found significant at difference was noticed in the Concentration ability. In the physiological parameters, the aforementioned five main variables were mapped but there was no significant difference.